PENGEMBANGAN MODUL TEKNIK JUMPUTAN MATA KULIAH ANALISIS TEKSTIL PADA PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Oktaviani, Vina; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of the research as an effort to solve the college students problem in Textile Analysis lectures at Pinching Tecnique.Thereare the difficulties in making pattern/motif and coloring process of pinching fubric. This purpose head for resulting media in valid and practical. This research was known as Research & Development (R&D). The research procedures include define, design and develop stages. The data was from validity test, small group and big group of college students practicallity test, and advisor of Textile Analysis leature subject. The validity test given to 3 validator, practicallity test given to 10 college students, big group practicallity test given to 30 college students and given to 1 advisor of Textile Analysis lectures subject. Based validity test the researcher got score 4,56 which categorized as valid. The result of practicallity test from small group was got score 78,50% which categorized as practical, big group test was got score 80,04% which categorized as very practical and test from advisor of lectures subject was got score 83,33% which categorized as very practical. So this module is proper to use as learning media.Keyword: Module, Pinching Tecnique, Valid and Practical.